FARS2 mutations presenting with pure spastic paraplegia and lesions of the dentate nuclei. Issue 9 (14th August 2018) - Sahai, Supreet K.; Steiner, Rebecca E.; Au, Margaret G.; Graham, John M.; Salamon, Noriko; Ibba, Michael; Pierson, Tyler M.
Abstract: Mutations in FARS2, the gene encoding the mitochondrial phenylalanine‐tRNA synthetase (mtPheRS), have been linked to a range of phenotypes including epileptic encephalopathy, developmental delay, and motor dysfunction. We report a 9‐year‐old boy with novel compound heterozygous variants of FARS2, presenting with a pure spastic paraplegia syndrome associated with bilateral signal abnormalities in the dentate nuclei. Exome sequencing identified a paternal nonsense variant (Q216X) lacking the catalytic core and anticodon‐binding regions, and a maternal missense variant (P136H) possessing partial enzymatic activity. This case confirms and expands the phenotype related to FARS2 mutations with regards to clinical presentation and neuroimaging findings.